How land transfer marketization influence on green total factor productivity from the approach of industrial structure? Evidence from China - Lu, Xin-hai; Jiang, Xu; Gong, Meng-qi (Land use policy, 2020)
•LTM, industrial structure optimization and green TFP are integrated into a unified framework.•LTM, industrial structure rationalization and optimization all can improve green TFP, while their interactions would inhibit it in China.•There exist regional differences of the impact of LTM and industrial structure on green TFP across the regions in China. Market-oriented allocation of land resources is one of the main economic reforms in China. However, the influence of land transfer marketization (LTM) on green total factor productivity (green TFP) and its mechanisms remain unknown. Based on panel data of 30 provincial administrative regions in China from 2004 to 2016, this study attempts to establish mechanism among LTM, industrial structure and green TFP, which is measured by the Slack Based Measure DEA (SBM-DEA) model containing undesirable output, and empirically estimates the impact of LTM, the rationalization and optimization of industrial structure and their interactions on green TFP further. The results show that: 1) LTM has a significant promoting effect on the improvement of green TFP in China, and the effect is also significant in the eastern, central and western regions as well, indicating that the application of land transfer policy to regulate regional economic development is widespread in China. 2) The rationalization of industrial structure has significantly promoted the development of green TFP in China, as well as at the regional levels, and the effect decreases from the western region to the central and eastern regions. The optimization of industrial structure also has a promoting effect on green TFP in China and all the regions, but the regional differences of the effect are contrary to that of the rationalization of industrial structure, with a decreasing trend from the eastern region to the central and western regions. 3) The interaction between LTM and the rationalization of industrial structure has significantly inhibited the improvement of green TFP in China, and the regional variations of the restraining effect are higher in the western region, followed by the central and eastern regions. The interaction between LTM and the optimization of industrial structure also has a negative effect on green TFP in China, and the regional variations of the effect showing the decreasing trend from the eastern region to the western and central regions. Therefore, China should continue to adhere to the market-oriented urban land transfer system reform, actively play the role of the government in the industrial upgrading and industrial transfer, and formulate a differentiated land transfer system and industrial development policies based on the economic development and industrial characteristics of various regions, so as to achieve the sustainable development of China’s economy and society.